Profil Isolat Corynebacterium diphtheriae Toksigenik di Jawa Timur Tahun 2012-2017 - Sugi Deny Pranoto Soegianto; Adi Pramono Hendrata; Eveline Irawan; Ismoedijanto; Dominicus Husada (PENGURUS BESAR IKATAN DOKTER INDONESIA (PB IDI), 2019)
Introduction: Diphtheria has been reported as an outbreak in some regions inIndonesia, most of the cases are from East Java.Objective: To describe the profile of toxigenic Corynebacterium diphtheriaeisolates in East Java. Methods. An descriptive study from August 20th -November 30th, 2018. Isolates was selected by cluster random sampling. The viability and toxigenicity testwere done in BBLK Surabaya. Viable and toxigenic isolates were done forcharacteristic analysis. Result: A total of 114 isolates, 6 were non-viable, 108 were viable and toxi-genic. The majority of the hosts were male (58,3%), median age 6,5-year-old(minimum 1, maximum 14-year-old), 50% from the 1-5-year-old age group. Highest origin of isolates from patients (78,7%) rather than carriers (21,3%).The most isolates from Madura (47,2%) and horseshoe area (20,4%). Most ofthem (74.1%) were taken from a pharyngeal swab rather than a nasal swab(25,4%). Mitis was 76,9% and gravis was 23,1%. Conclusion: In this study, the majority of toxigenic Corynebacterium diphtheriae were found in the 1-5-year-old age group and most of them domi-cile in Madura and horseshoe area. Most of the isolates were taken from apharyngeal swab of patients. Mitis was the major variant.